PERMASALAHAN KELUARGA PASCA BENCANA BANJIR (Studi Kasus Desa Blanting, Kecamatan Sambelia, Kab. Lombok Timur) - Ruaida Murni (Puslitbangkesos Kementerian Sosial RI, 2010)
Natural disaster in form of a flood that was occurred in Desa Blanting leaving behind many issue for the victims' families that were affected lYy this natural disaster. To do efforts to restore the victims of natural disasters to their normal conditions, first we must know what problems they are faced. The purpose of this study was to describe any problems encountered by the families of the natural disaster victims in DesaÂ Blanting on post-flood disaster. The type of this research is descriptive qualitative study. The location of thisstudy was determined by purposive method, is one of the areas affected by natural disasters in the Province of West Nusa Tenggara. The selection of informants involved in this research done purposively. Data collected through in-depht interviews with 5 leader of disaster victims' families. FGD wad done with local communihJ leaders, village leader, the Social Service Manpower and Transmigration and Tagana East Lombok, and observation and documentation study. The results showed that the problems faced by families after the floods, associated with major job losses, heavily damaged home, traumatic children, child education and health. The result of these issues is that all of the flood victims' families are prone to social and economicproblems. While the existing natural resource potential only able to overcome the problem shortly. Suggestions from this study are: relevant agencies immediately restore the condition of agricultural land as theÂ main job, recovering trauma in children and immediate repair of heavily damaged homes. Need to empower families to improve the socio-economic welfare families post-flood disaster. Need assistance from social workers in disaster victims recovery.